SURFACE PLASMON RESONANCE (SPR) CURVATURE PHENOMENON USING OTTO CONFIGURATION AS SATURATED AND UNSATURATED FATTY DETECTION ON CHOLESTEROL FOOD - Fatimah Nopriardy; Lufsyi Mahmudin; Kamsul Abraha; Edi Suharyadi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Surface Plasmon Resonance (SPR) on thin layer of conductive 50:1 PVA-coated silver nanoparticles ( AgNPs@PVA ) 0.02 M on 11-20 nm using Otto Configuration have been observed for monitoring cholesterol level of crude palm oil time-cooking for food-cholesterol. Its has been proved gap between prism/air/silver on 850 nm. Surface Plasmon Resonance (SPR) phenomenon analyzed by HeNe laser on ( = 632,8 nm ). SPR curvature has been showed by observing reflectance of laser incident angle variation on the prism. SPR angle for the prism/Ag system is (44.4 ± 0.05)° with the reflectance value on 0.8. Due to the addition of AgNPs@PVA ,also after the reaction for one-time cooking of with quail eggs ( high-cholesterol/high-unsaturated fatty ), SPR angle shifts to (47,8 ± 0.05)° with the reflectance value on 0.58 using MATLAB simulation. The shifting on SPR angle shows that the sensitivity SPR is a biosensor. Keywords : surface plasmon resonance (SPR), Otto configuration, cholesterol food.